Probing Electronic Coherence between Core-Level Vacancies at Different Atomic Sites - Jun Wang; Taran Driver; Paris L. Franz; Přemysl Kolorenč; Emily Thierstein; River R. Robles; Erik Isele; Zhaoheng Guo; David Cesar; Oliver Alexander; Sandra Beauvarlet; Kurtis Borne; et al. (Physical Review X, 2025)
The detailed understanding of electronic coherence in quantum systems requires measurements on the attosecond timescale. Attosecond x-ray pulses enable the study of electronic coherence in core-excited molecular systems. Here we report on the coherent motion of electrons in the 1,1-difluoroethylene ion following ionization of the K shell of the two nonequivalent carbon sites with a subfemtosecond x-ray pulse. Using the angular streaking technique to track the Auger-Meitner decay, we observe temporal modulations of the emission, indicating the electronic coherence of the core-excited ionic states, and extract a 6.5±0.8  fs average lifetime of the core-level vacancies. A quantum-mechanical model is employed to interpret the measurement, and we find the observed temporal modulations are independent of charge density oscillations. This work opens a new regime of coherent electronic motion, beyond charge migration, where electronic coherence manifests in the nonlocal quantum correlation between atomic sites while charge density oscillation is absent. Our results broaden the landscape of electronic coherence in molecular systems.